1985
DOI: 10.1136/bmj.290.6466.455
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of the elderly: 1--Settings and services.

Abstract: A man who insisted on having his hat taken off by the staff of his residential home after hours at the day hospital doing things for himself illustrates one of the challenges of geriatric rehabilitation: someone may be encouraged to do more than he Physiotherapists and occupational therapists are obvious essentials for many elderly people in hospital; but a national study of resources in geriatric medicine has shown that numbers of both are quite inadequate and not likely to become adequate.'0 A special grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A published work review identified risk factors most likely to predispose to a placement discharge 1–9 . The most common factors relevant to our patient group were chosen for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A published work review identified risk factors most likely to predispose to a placement discharge 1–9 . The most common factors relevant to our patient group were chosen for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Rehabilitation goals should be patient‐centered and based on multidisciplinary assessment 1 . Isaacs stated that the aims of rehabilitation should include, “the restoration of lost function and the person's former role; maximal use of remaining function and attainment of an altered role; or adaptation to reduced function and a reduced role” 1 . Patients offered rehabilitation are more likely to be discharged into the community 2 .…”
Section: Introductionmentioning
confidence: 99%
“…At the Royal East Sussex Hospital, Hastings, UK, an elderly orthopaedic patient automatically attends a 'total care' clinic pre-and post-surgery. 32 Gloag also mentions the use of volunteers who visit the home after hospitalisation in another hospital in North London. Suttom describes a new 'Homeward Bound Unit' in Newham, East London, UK.…”
Section: Improving Functional Statusmentioning
confidence: 98%
“…A volunteer who visits patients living alone on the day of discharge and during the first fortnight, to chat, do chores, establish liaisons and report to the social worker, can be a useful addition to the team. 114 Predischarge flats within rehabilitation units can be used for assessment and, if the carer is also admitted, for training of the carer. 114 Aids and adaptations should be promptly supplied.…”
Section: Discharge From Hospitalmentioning
confidence: 99%
“…114 Predischarge flats within rehabilitation units can be used for assessment and, if the carer is also admitted, for training of the carer. 114 Aids and adaptations should be promptly supplied. Handicapped people over 65 often lack bath and toilet aids.…”
Section: Discharge From Hospitalmentioning
confidence: 99%